Peta Kekuatan Partai Islam dalam Empat Era Pemerintahan di Indonesia - Ruslan Ismail Mage (Universitas Nasional, 2018)
Map of the Strength of Islamic Parties in the Four Governments Era in Indonesia. This writing uses library research methods. The problem in this paper is how the strength of Islamic-based Political Parties in Indonesia in four eras of government, namely the Parliamentary Democracy era (1950-1959), Guided Democracy (1959-1965), New Order (1965-1998), and Reformation (1999-Present )? His findings are that Islam-based political parties cannot be separated from the three time dimensions of the Indonesian people, past, present and future. Since the first elections in 1955 until the 2014 election, it has always been an important part of Indonesia's political process, although it has never been the winner of the election. So long as there is a community organization based on Islam, during this time the Islamic party will always exist and fly in Indonesian politics. Keywords: Islamic party, parliamentary, guided democracy, new order, reform